Improving Basketball Dribbling Ability through Ball Handling Exercises - Irfan Arifianto; Adnan Fardi; Sari Mariati (Universitas Negeri Padang, 2021)
Dribbling is a basic technique that basketball players must have. The low ability of dribbling when playing basketball, so that players often lose the ball when competing is a problem studied in this study. One form of training that must be given in strengthening dribbling skills is ballhandling training. By providing this training, it is hoped that players will be able to play well, especially keeping the ball under control because of their good dribbling skills. This study aims to determine the effect of ballhandling training on dribbling skills. The sample used is students of one of the high school in Payakumbuh participating in basketball extracurricular activities totaling 10 people. After the pre-test was carried out, all samples were treated with ballhandling exercises. The research implementation consisted of 16 meetings. The results showed that ballhandling training in basketball training had a major effect on increasing dribbling ability (thit = 11.21> ttab = 2.26). For this reason, for further research, researchers should use ballhandling exercises using smaller balls in early childhood so that the fundamentals in playing basketball can be more strongly implanted.